2021
DOI: 10.1177/2050313x211036777
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic gall bladder: A case report

Abstract: Ectopic gall bladder under the left lobe of liver is a rare congenital anomaly of the position of gall bladder, which is mostly detected during surgery and causes technical difficulty at the time of operation. We operated a 64-year-old male who presented with gall stone disease and pre-operative ultrasound did not report any abnormality in position. On laparoscopy, it was found to be attached on the left side of falciform ligament under segment III. It was a true ectopic gall bladder without situs inversus. Ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…13 It is very rare and includes three anatomic abnormalities: a right-sided ligamentum teres, an ectopic left-sided gallbladder, and a situs inversus. 16 The possible associated abnormalities with the left-sided gallbladder are portal vein anomalies, biliary system anomalies, and left lobe hypoplasia. 17 It has been reported that the likelihood of intraoperative bile duct injuries in individuals with left-sided gallbladder is higher than the average population (up to 7.3%) due to anomalies of the bile duct, portal vein, and other anatomical structures in the hepatobiliary system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 It is very rare and includes three anatomic abnormalities: a right-sided ligamentum teres, an ectopic left-sided gallbladder, and a situs inversus. 16 The possible associated abnormalities with the left-sided gallbladder are portal vein anomalies, biliary system anomalies, and left lobe hypoplasia. 17 It has been reported that the likelihood of intraoperative bile duct injuries in individuals with left-sided gallbladder is higher than the average population (up to 7.3%) due to anomalies of the bile duct, portal vein, and other anatomical structures in the hepatobiliary system.…”
Section: Discussionmentioning
confidence: 99%
“…The reported incidence of this anomaly is estimated to be between 0.1% and 1.2% 13 . It is very rare and includes three anatomic abnormalities: a right‐sided ligamentum teres, an ectopic left‐sided gallbladder, and a situs inversus 16 . The possible associated abnormalities with the left‐sided gallbladder are portal vein anomalies, biliary system anomalies, and left lobe hypoplasia 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Normally gallbladder is located in the gallbladder fossa under the right lobe between segments IV and V of the liver [9] .…”
Section: Discussionmentioning
confidence: 99%